Cryoablation as a first-line therapy for atrial fibrillation: current status and future prospects. (3rd August 2022) - Andrade, Jason G.; Deyell, Marc W.; Dubuc, Marc; Macle, Laurent
ABSTRACT: Introduction: Atrial fibrillation (AF) is a common chronic and progressive heart rhythm disorder. For those in whom sinus rhythm is desired, contemporary clinical practice guidelines recommend antiarrhythmic drugs (AADs) as the initial therapy. However, these medications have modest efficacy and are associated with significant adverse effects. Areas Covered: The current article reviews the evidence surrounding first-line catheter ablation, particularly the emerging evidence surrounding the use of cryoballoon ablation as a first-line therapy. The focus of the review is on the outcomes of arrhythmia freedom, quality of life, health-care utilization, and safety. In addition, the article will review novel cryoablation systems. Expert Opinion: Recent evidence suggests that cryoballoon ablation significantly improves arrhythmia outcomes (e.g. freedom from any atrial tachyarrhythmia or symptomatic atrial tachyarrhythmia, reduction in arrhythmia burden), patient-reported outcomes (e.g. symptoms and quality of life), and health-care resource utilization (e.g. hospitalization), without increasing the risk of adverse events. These findings are relevant to patients, providers, and health-care systems, as they help inform the decision-making regarding the initial choice of rhythm-control therapy in patients with treatment-naive AF.